Pengembangan Bisnis UMKM Kopi Lelet Melalui Peningkatan Kapabilitas Manajerial dan Kapasitas Produksi di Kabupaten Rembang - Hersugondo Hersugondo; Ahyar Yuniawan; Idris Idris (Surya Abdimas, 2019)
Coffee is one drink that is very popular with people in the world. Coffee produced and consumed by the Rembang public is called Kopi Lelet. Lelet coffee is typical Rembang coffee. Lelet coffee is identical to the activity of nglelet with the media of cigarettes and the ink uses lethekan (pulp) lelet coffee. SMEs that produce lelet coffee is Cap Cangkir and Cap Leo Lelet coffee. However, both SMEs have obstacles in developing their business, namely: 1) Limited insight and knowledge about management and entrepreneurship owned by Kopi Lelet SMEs; 2) The production process is still manual, not using a machine so the production results are still limited; 3) Marketing areas are still limited in Rembang Regency and conventional with still simple packaging; 4) Financial management is not good, income is still used for daily needs; and 5) Limited capital owned by partner coffee lelet SMEs, especially for the procurement of production equipment. To overcome these problems, the team undertook the following activities: 1) Conducting entrepreneurship training and business management; 2) Facilitating the procurement of coffee grinding machines and packaging presses; 3) Facilitating the procurement of product packaging with attractive designs; and 4) Business assistance for Kopi Lelet SMEs partner especially recording business transactions. The results of these community service activities are: 1) Lelet coffee partners SMEs can implement good business management; 2) Availability of coffee grinders and packaging presses; 3) Availability of attractive product packaging; and 4) Lelet coffee partner SMEs already has a simple bookkeeping.